Cephalometric Mandibular Dimensions in Growing Turkish Children: Trends of Change, Sex-Specific Differences, and Comparisons with Published Norms - Hande Pamukçu; Nilüfer İrem Tunçer; İsmail Can Pelin; Hatice Yağmur Zengin (Galenos Yayinevi, 2022)
Objective: The aims of this study were to investigate cephalometric mandibular dimensions in growing Anatolian Turkish children and to identify the periods of rapid growth for boys and girls. Furthermore, the secondary aim was to compare obtained values with published standards in the literature.Methods: A total of 528 pretreatment lateral cephalometric radiographs, grouped according to age and sex, were analyzed. Effective mandibular length, ramus height, and corpus lengths were comparatively evaluated within age groups for boys and girls and between sexes for the same age group. Data acquired from this study were compared with American, Canadian, Chinese, and European norms. Growth curves for mandible were constructed for each sex group.Results: Effective mandibular length was almost always significantly longer in boys, except for 9- and 12-year-age groups. Effective mandibular length in girls increased significantly between ages 8 and 10, 10 and 12, and 11 and 13 years, while in boys between ages 8 and 10, 9 and 11, and 13 and 15 years. Turkish girls had significantly shorter effective mandibular lengths than American girls at age 14. No significant difference was found between Turkish and Chinese girls and boys. Turkish girls and boys had significantly shorter corpus lengths from their Norwegian counterparts at age 12.Conclusion: Except for 9- and 12-year-age groups, effective mandibular length was almost always significantly longer in boys compared to the girls. It is suggested to use norm values from more recently conducted studies and which are representative of the studied population. Growth curves can be used to predict the approximate mandibular dimensions at a particular age.